2002
DOI: 10.1002/jcla.2058
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex polymerase chain reaction: A practical approach

Abstract: Considerable time and effort can be saved by simultaneously amplifying multiple sequences in a single reaction, a process referred to as multiplex polymerase chain reaction (PCR). Multiplex PCR requires that primers lead to amplification of unique regions of DNA, both in individual pairs and in combinations of many primers, under a single set of reaction conditions. In addition, methods must be available for the analysis of each individual amplification product from the mixture of all the products. Multiplex P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
346
0
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(364 citation statements)
references
References 29 publications
2
346
0
16
Order By: Relevance
“…13 RT-PCR technology is not affected by these limitations because it is dependent on the presence of viral nucleic acid rather than infectious or intact virions. 18 The incorporation of an internal control in a PCR reaction is highly desirable, and we included human ERV to monitor inhibition of the PCR. However, our results showed that the majority of respiratory specimens do not contain inhibitory substances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 RT-PCR technology is not affected by these limitations because it is dependent on the presence of viral nucleic acid rather than infectious or intact virions. 18 The incorporation of an internal control in a PCR reaction is highly desirable, and we included human ERV to monitor inhibition of the PCR. However, our results showed that the majority of respiratory specimens do not contain inhibitory substances.…”
Section: Discussionmentioning
confidence: 99%
“…However, PCR may be affected by the presence of sequence variation that can be overcome by designing the assay to target highly conserved nucleic acid sequences. 18 Also, using conventional PCR technology to detect several viruses individually is labor-intensive and expensive. 18,19 These limitations can be overcome by using a multiplex PCR assay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common problem is that quite a number of primers have to be used in the same reaction tube or well and these molecules may interact with each other, which may block the reaction [7,9,10,14,22]. A further problem may be the reliable identification of the various PCR products.…”
Section: Discussionmentioning
confidence: 99%
“…Initial surface-based amplification cycles are then coupled to efficient solution-phase PCR using one common primer pair. We demonstrate this method by coamplifying and genotyping 75 unselected human single-nucleotide polymorphism (SNP) loci.The key challenge in developing a high-multiplex amplification procedure is preventing excessive off-target priming by the many primers in the reaction [1][2][3] . Several previously developed methods use surface immobilization of primer pairs as a way to separate reactions and thus limit primerdimer formation [4][5][6] , but drawbacks of these methods include inefficient amplification, loss of reactants from the surface and considerable primer-dimer formation within pairs of primers.…”
mentioning
confidence: 99%